The Effect of Sleep Quantity and Quality on Adults\' Blood Pressure: Yazd, 2014-2015 - Hossein Fallahzadeh (Journal of Community Health Research, 2017)
Introduction: Sleep is an essential part of life and is of utmost importance in preserving human health and performance. The quantity and quality of sleep can affect blood pressure. The objective of this paper was to determine the relationship of sleep quantity and quality with high blood pressure.